Underwater image enhancement - Kua, Bella Jing Xuan (2017)
The ocean is very vast and it makes up seventy percent of the Earth’s surface yet, less than five percent of the ocean have been discovered and explored. In this technology inclined generation, inventions and creations are created to enable humans to take images and footage underwater. The purpose of capturing and recording of underwater images are endless, ranging from research and study purposes to leisure uses or even tracking an animal species. Hence, the quality of the underwater images captured is very essential.